Evolutionary developmental biology - Sears, Karen (Henry Stewart Talks, 2023)
Evolutionary developmental biology, Evolution of the tetrapod limb, Digit reduction in mammals, Modern synthesis, Phenotypic integration and modularity, The generation of variation, Origin of morphological innovation, Novel structures: beetle horns